Mendelian randomization analyses for PCOS: evidence, opportunities, and challenges. Issue 5 (May 2022) - Wang, Congying; Wu, Wei; Yang, Haiyan; Ye, Zhenhong; Zhao, Yue; Liu, Jun; Mu, Liangshan
Abstract : Identifying etiological risk factors is significant for preventing and treating patients with polycystic ovary syndrome (PCOS). Through genetic variation, Mendelian randomization (MR) assesses causal associations between PCOS risk and related exposure factors. This emerging technology has provided evidence of causal associations of anti-Müllerian hormone (AMH) levels, sex hormone-binding globulin (SHBG) levels, menopause age, adiposity, insulin resistance (IR), depression, breast cancer, ovarian cancer, obsessive-compulsive disorder (OCD), and forced vital capacity (FVC) with PCOS, while lacking associations of type 2 diabetes mellitus (T2DM), coronary heart disease (CHD), stroke, anxiety disorder (AD), schizophrenia (SCZ), bipolar disorder (BIP), and offspring birth weight with PCOS. In this review, we briefly introduce the concept and methodology of MR in terms of the opportunities and challenges in this field based on recent results obtained from MR analyses involving PCOS. Highlights: The key to preventing and treating polycystic ovary syndrome (PCOS) is to identify adjustable risk factors. Mendelian randomization (MR) is an emerging field that uses genetic variants to assess causal associations between modifiable exposures and outcomes. It can effectively avoid reverse causation and save manpower, reducing material and financial costs in the meantime. MR analysis of PCOS has provided evidence for causal associations between PCOS and various factors, including anti-Müllerian hormone level, sex hormone-binding globulin level, menopause age, adiposity, insulin resistance, depression, breast cancer, ovarian cancer, obsessive-compulsive disorder, and forced vital capacity . Current MR analyses did not support the causal association with PCOS in several disorders, such as type 2 diabetes mellitus, coronary heart disease, stroke, anxiety disorder, schizophrenia, and bipolar disorder, as well as offspring birth weight.